Meningkatkan Hasil Belajar Siswa Menggunakan Model Pembelajaran Problem Based Learning Pada Materi Relasi Dan Fungsi - Suparman M Ismail; Perry Zakaria; Dewi Rahmawaty Isa (Jambura Journal of Mathematics Education, 2023)
This study aims to improve student learning outcomes using the Problem Based Learning model on relations and functions material. This classroom action research was attended by 29 students of class VIII.2 for the 2022/2023 academic year. In practice, the data collected was obtained through observation and tests. As for the data analysis technique in the form of data analysis of teacher observations, student observations and tests of student mathematics learning outcomes. Referring to the procedures followed, the research stages involved include planning, implementing, observing, reflecting. The research consisted of two cycles. The results showed that the results of students' mathematics learning in cycles I and II were 55.18% and 86.20% with an increase from less to very good criteria. From observations of teacher activities when managing learning there was an increase, in cycle I it reached 79.42% good criteria, while cycle II was very good, the percentage of achievements was 97.06%. The results of observations of student activities have increased, from the first cycle the percentage is 56.25% good criteria and the second cycle is 93.75%, very good. This means that learning using the Problem Based Learning model in relation and function material is able to improve students' mathematics learning outcomes.